PENERAPAN PROGRAM BAHASA ARAB DALAM PEMBELAJARAN MAHARAH AL KALAM DI SMA IT INSAN MULIA BOARDING SCHOOL PRINGSEWU, LAMPUNG: Indonesia - Toponi, Meizar; Aulia, Maya; Masrur, Mohammad (Jurnal Pendidikan Bahasa Arab L-DHAD, 2023)
AbstractIn the context of learning Arabic, mahārat al-kalām is the main skill that must be mastered by students and is one of the ultimate goals of learning a foreign language. The mahārat al-kalām learning course at SMAIT Insan Mulia Boarding School Pringsewu Lampung has not shown results that describe students' Arabic language skills actively and productively. In accordance with the background of the problems described above, the authors formulate the problem in this paper is "How is the application of the Arabic language program in learning Maharah Al Kalam at the Smait Insan Mulia Pringsewu Islamic Boarding School, Lampung?Speaking skill (maharah al-kalam/speaking skill) is the ability to express sounds or words that are articulated to express thoughts in the form of ideas, opinions, desires, or feelings to the other person. In a broad sense, the results of writing state that to improve speaking skills students are equipped with basic speaking skills that are very necessary when working in the field, such as practicing the application of dialogue patterns, vocabulary, rules, facial expressions, and so on. There are several techniques that can be used in this exercise, including: dialogue (al-hiwar), pattern practice (tathbiq alnamudzaj), and oral composition (al-tarkib al-syafawi).